Analisis Kapasitas Tanah Menahan Air (Water Holding Capacity) pada Penambahan Biochar Berbahan Pelepah Kelapa Sawit (Elaeis guineensis Jacq) - Akbar, Fahri Andrian; Suharyatun, Siti; Amien, Elhamida Rezkia; Tusi, Ahmad (Jurnal Agricultural Biosystem Engineering, 2024)
The availability of water in the soil varies and is influenced by soil properties, especially those related to the soil's capacity to retain water. Water retention capacity is one of the primary functions of soil, playing a crucial role in maintaining moisture and distributing water to plants. This research aims to analyze the effects of dosage and particle size of oil palm frond biochar on soil infiltration and water retention capacity. The study employed a Completely Randomized Factorial Design (RALF), comprising two factors: the dosage of oil palm frond biochar (A) and the biochar particle size (B). The dosage factor consisted of three levels: 0% (A1), 0.6% (A2), and 1.2% (A3), while the biochar particle size factor consisted of three levels: < 0.5 mm (B1), 0.5 - 1 mm (B2), and 1 - 2 mm (B3). Each experimental unit was replicated three times, resulting in 27 experimental units. The study utilized soil with silt loam texture. The research parameters observed included soil water content at field capacity conditions (pF 2.54) and at permanent wilting point conditions (pF 4.2), changes in water content over time, mass density, particle density, porosity, water infiltration, and water retention capacity. The findings revealed that the addition of biochar to silt loam textured soil resulted in a reduction in infiltration rate, with the most significant reduction observed when applying biochar with a particle size < 0.5 mm (B1). Furthermore, providing biochar with a size of 0.5 – 1 mm at a dosage of 0.6% (B2A2) and a dosage of 1.2% (B2A3) had the effect of increasing the soil's water retention capacity. Keysword : Infiltration, Factorial Completely Randomized Design, Silt Loam, Soil Physical Properties.